P100 The Feasibility Of Using Commercial Multiple Breath Nitrogen Washout Devices In School-aged Children. (10th November 2014) - Raywood, E; Duncan, J; Legg, S; Aurora, P; Stocks, J
Abstract : Background: Multiple breath inert-gas washout (MBW) using sulphur hexafluoride (SF6 ) measured by mass spectrometry (MS), is sensitive to early lung disease in children with Cystic Fibrosis (CF) 1 but is not widely available. To increase the accessibility of MBW, commercial devices have been adapted using nitrogenwashout (N2 -MBW). Our aim was to assess the feasibility of two commercial N2 -MBW devices as supplied by the manufacturers compared to a custom-built MS system in school-aged children. Methods: Patients with CF and controls performed MBW on three devices; the Exhalyzer ® D (ECO MEDICS AG); the EasyOne Pro ® LAB (ndd Medizintechnik AG) and the MS system (AMIS 2000, Innovision ApS) on the same test occasion (order randomised). Attempts were made to obtain 3 technically acceptable runs/device (maximum 8 attempts on each). During testing children watched a DVD and were encouraged to breathe normally. Data were analysed using the 'clinical application' setting for both commercial devices, and customised software for the MS. Quality control was in accordance with the ATS/ERS consensus statement 1 and manufacturers' guidelines. Results: 14 control (mean[range]age: 15.0[12.5–16.7]yrs) and 18 children with CF (13.5[7.8–17.4]yrs) were assessed. The median (range) number of runs attempted were: MS 3(3–8), Exhalyzer ® D 4(3–6), EasyOne Pro ® LAB 4(3–8). Average calibration time was shorter for EasyOne Pro ® LAB (5 min) than either MS (11 mins) or Exhalyzer ® D (12 min). Total test duration was similar between devices and dependent on disease severity. 3 acceptable MBW runs were achieved in all children using the MS, 75% with the EasyOne Pro ® LAB, and 47% on the Exhalyzer ® D system (see Table ). Reasons for failure with Exhalyzer ® D were usually due to technical/equipment problems, whereas for the EasyOne Pro ® LAB these were generally associated with marked changes of breathing pattern at commencement of washout, leading to exclusion of one or more runs. Discussion: Despite use in an experienced MBW centre, our initial attempts to implement commercial MBW devices according to manufacturers' guidelines resulted in a relatively low success rate in schoolchildren when compared to MS. Subsequent feedback to manufacturers has led to further adaptations which should improve feasibility in future, although this has yet to be assessed in very young children. Reference: Robinson et al . Eur Resp J 2013